Dysregulated A to I RNA editing and non-coding RNAs in neurodegeneration - Singh, Minati (Frontiers in Genetics, 2013)
RNA editing is an alteration in the primary nucleotide sequences resulting from a chemical change in the base. RNA editing is observed in eukaryotic mRNA, tRNA, rRNA, and non-coding RNAs. The most common RNA editing in the mammalian central nervous system is a base modification, where the adenosine residue is base-modified to inosine (A to I). Studies from ADAR mutants in C. elegans, Drosophila, and mice clearly show that the RNA editing process is an absolute requirement for nervous system homeostasis and normal physiology of the animal. Understanding the mechanisms of editing and findings of edited substrates has provided a better knowledge of the phenotype due to defective and hyperactive RNA editing. A to I RNA editing is catalyzed by a family of enzymes knows as ADARs (adenosine deaminase that act on RNA). ADARs modify duplex RNAs and editing of duplex RNAs formed by non-coding RNAs can impact RNA functions, leading to an altered regulatory gene network. Such altered functions by A to I editing is observed in mRNAs, microRNAs (miRNA) but other editing of small and long non-coding RNAs has yet to be identified. Thus, non-coding RNAs (ncRNA) and RNA editing may provide key links between neural development, nervous system function, and neurological diseases. This review includes a summary of seminal findings regarding the impact of ncRNAs on biological and pathological processes, which may be further modified by RNA editing. NcRNAs are non-translated RNAs classified by size and function. Known ncRNAs like miRNAs, smallRNAs (smRNAs), PIWI-interacting RNAs (piRNAs) and long non-coding RNAs (lncRNAs) play important roles in splicing, DNA methylation, imprinting, and RNA interference. Of note, miRNAs are involved in development and function of the nervous system that is heavily dependent on both RNA editing and the intricate spatiotemporal expression of ncRNAs. This review focuses on the impact of dysregulated A to I editing and ncRNAs in neurodegeneration.